Thermodynamic and economic investigations of transcritical CO2-cycle systems with integrated radial-inflow turbine performance predictions - Song,J; Li,X; Ren,X; Tian,H; Shu,G; Gu,C; Markides,CN (Applied Thermal Engineering, 2020)
Transcritical CO2 (TCO2) cycle systems have emerged as a promising power-generation technology in certain applications. In conventional TCO2-cycle system analyses reported in the literature, the turbine efficiency, which strongly determines the overall system performance, is generally assumed to be constant. This may lead to suboptimal designs and optimization results. In order to improve the accuracy and reliability of such system analyses and offer insight into how knowledge of these systems from earlier analyses can be interpreted, this paper presents a comprehensive model that couples TCO2-cycle calculations with preliminary turbine design based on the mean-line method. Turbine design parameters are optimized simultaneously to achieve the highest turbine efficiency, which replaces the constant turbine efficiency used in cycle calculations. A case study of heat recovery from an internal combustion engine (ICE) using a TCO2-cycle system with a radial-inflow turbine is then considered, with results revealing that the turbine efficiency is influenced by the system’s operating conditions, which in turn has a significant effect on system performance in both thermodynamic and economic terms. A more generalized heat source is then considered to explore more broadly the role of the turbine in determining TCO2-cycle power-system performance. The more detailed turbine-design modelling approach allows errors of the order of up to 10-20% in various predictions to be avoided for steady-state calculations, and potentially of an even greater magnitude at off-design operation. The model allows quick preliminary designs of radial-inflow turbines and reasonable turbine performance predictions under various operating conditions, and can be a useful tool for more accurate and reliable thermo-economic studies of TCO2-cycle systems.